2017
DOI: 10.1111/apa.13735
|View full text |Cite
|
Sign up to set email alerts
|

Assessments carried out by a child abuse and neglect team in an Amsterdam teaching hospital led to interventions in most of the reported cases

Abstract: Our results showed that CAN affected more than one in every 100 children visiting our hospital, and the expertise of our hospital-based CAN Team led to an intervention in the majority of the reported cases. The broad scope of problems that were encountered underlined the importance of a multidisciplinary CAN team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Our results show that most European hospitals have no standard procedures or strategies, such as a child maltreatment policy officer, child maltreatment team, registering system, regular meetings with child protective services, e-learning exercises and training programmes, in place to facilitate the recognition of child maltreatment nor to monitor or refer when necessary [35][36][37]. In previous research, physicians stated that even though a protocol for suspected child maltreatment was present, the majority did not know where to find it or how to use it in practice [38].…”
Section: Plos Onementioning
confidence: 88%
“…Our results show that most European hospitals have no standard procedures or strategies, such as a child maltreatment policy officer, child maltreatment team, registering system, regular meetings with child protective services, e-learning exercises and training programmes, in place to facilitate the recognition of child maltreatment nor to monitor or refer when necessary [35][36][37]. In previous research, physicians stated that even though a protocol for suspected child maltreatment was present, the majority did not know where to find it or how to use it in practice [38].…”
Section: Plos Onementioning
confidence: 88%
“…Assessing aggregate information coded from medical provider notes provides a useful overview of trends in cases evaluated for child abuse and neglect, as demonstrated by previously published studies that have similarly extracted information from child abuse pediatrician (CAP) case notes. Coded data have been used by researchers to identify different notetaking approaches used by CAPs (Keenan & Campbell, 2015), to provide descriptive data on the incidence of child abuse and neglect cases and subsequent interventions in the Netherlands (Teeuw et al, 2017), to investigate legal consequences of child abuse (Hendrix et al, 2020), and to describe medical consultations by CAPs in a hospital setting in the U.S. (Hicks et al, 2020; Johnson et al, 2021). While previous studies were conducted primarily by medical professionals, our interdisciplinary team included diverse perspectives from researchers in health policy, public health, social work, and developmental psychology, in addition to medical providers.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that expert consultation has added value to patient care in cases of suspected child abuse 10 16 17. However, Lindberg et al showed that even between child abuse paediatricians there was a significant variability in assessing the likelihood of child abuse 18.…”
Section: Discussionmentioning
confidence: 99%